Dynamics of general physical fitness indicators in the system of physical therapy of 11-13-year-old women weightlifters after traumatic injuries of the musculoskeletal system - E. Yu. Doroshenko; A. A. Orlov; O. Ye. Chernenko; A. M. Hurieieva; I. V. Shapovalova; V. I. Hlukhykh; S. H. Polskyi; I. O. Sazanova; M. M. Syromiatnykov (Zaporozhye State Medical University, 2021)
The aim of the work to determine the dynamic characteristics of overall physical condition indicators in 11-13-year-old female weightlifters after injuries of the musculoskeletal system at the training stage of physical therapy. Materials and methods. The experimental population comprised 45 female weightlifters (aged 11-13 years, qualification ‒ I, II, III junior categories) from SСYSSOR "Spartak" of the Zaporizhzhia regional council, CYSS "Kolos" of Kamiansko-Dniprovskyi district of Zaporizhzhia region, Berdiansk CYSS of Zaporizhzhia Region City Council, and students of Kharkiv Regional Higher School of Physical Culture and Sports majoring in weightlifting. Patients after musculoskeletal injuries were divided into two groups: main (MG, n = 22) and control (CG, n = 23). Patients of the control group underwent standard treatment (generally prescribed in medical establishments). For main group patients in the training period, the program of physical therapy has been developed and implemented, with the current control of overall physical condition indicators. Research methods. Analysis of literature and sources of information presented on the Internet; clinical observations; pedagogical testing; methods of mathematical statistics. Results. Analysis of overall physical condition indicators of athletes of 11-13-year-old weightlifters of the main and control groups during the recovery and training periods allows us to state that main group athletes have higher growth rates, and dynamic characteristics of their overall physical condition are linear with constant focus on improvement. According to the indicators of "running 30 m, s" test, the following growth indicators were recorded: main group athletes (-0.48), control group athletes (-0.29), the difference (-0.19). According to the indicators of "standing long jump, cm" test, the following growth indicators were recorded: main group athletes (+14), control group athletes (+5), difference (+9). According to the results of the test "flexion-extension of the arms in the supine position, n" the following indicators were obtained: main group athletes (+4.44), control group athletes (+2.86), difference (+1.58). Conclusions. Intensification of the training process and forcing the training of junior athletes in weightlifting are the leading factors that result in injuries of the musculoskeletal system, multisystem pathologies and the development of pathomorphic phenomena. Indicators of overall physical condition of weightlifters aged 11-13 allow us to state that main group athletes have a higher difference in growth, and the tendency of their overall physical condition has a linear focus on improvement. Indicators of overall physical condition of control group athletes are nonlinear, according to "running 30 m, s" and "standing long jump, cm" the test results.